The effectiveness of nurse trainning program on nosocomial infection control in Vietnam - Thoa, Vo Thi Hong; Thu, Le Thi Anh; Tien, Nguyen Phuc; Van, Dang Thuy; Anh, Le Thi Kim; Trang, Dang Thi Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
None.